The Humid Condition (More) Overheated Observations - Pettman, Dominic (punctum books, 2020)
The Humid Condition: (More) Overheated Observations continues on the clicking heels of Dominic Pettman's Humid, All Too Humid (2016), providing a companion volume of pithy and witty observations for our overheated age. Covering topics from pop culture to academia to romance to politics to human mortality to everything in between, this collection of pointed musings aims to amuse, edify, instruct, provoke, tease, caution, and inspire. As with the first installment, the spirit of this book represents a fusion of Montaigne and Wilde; a mashup of Adorno and Yogi Berra; a parallel channeling of Marx and Marx (both Karl and Groucho). No doubt, Hannah Arendt would be appalled at the irreverence on display within these pages. Then again, "Heidegger has left the bildung." And as the author himself notes: "I have nothing new to say. And I'm saying it!"